1998
DOI: 10.1352/0047-6765(1998)036<0280:aiwsmr>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Are Individuals With Severe Mental Retardation and Multiple Disabilities Cost-Efficient to Serve Via Supported Employment Programs?

Abstract: The relations between cost-efficiency (from the perspective of worker, taxpayer, and society) and personal characteristics of supported employees (i.e., IQ, level of mental retardation, multiple disabilities, gender, ethnicity, and age) were examined. Results suggest that when sheltered workshops were used as alternative placements, supported employees with high IQs benefited more from employment within the community than did supported employees with lower IQs. From society's perspective, African American and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…That is, they might have produced a greater net benefit to taxpayers than supported employment. However, this is doubtful given the overwhelming amount of research that suggests supported employment produced more monetary benefits to all stakeholders (e.g., the employee, the taxpayer, and the society in general) than sheltered workshops (Baer, Simmons, Flexer, & Smith, 1995;Cimera, 1998;Conley, Rusch, McCaughrin, & Tines, 1989;Hill, Banks, Handrich, Wehman, Hill, & Shafer, 1987;Larson et al, 2007;Rusch, Conley, & McCaughrin, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…That is, they might have produced a greater net benefit to taxpayers than supported employment. However, this is doubtful given the overwhelming amount of research that suggests supported employment produced more monetary benefits to all stakeholders (e.g., the employee, the taxpayer, and the society in general) than sheltered workshops (Baer, Simmons, Flexer, & Smith, 1995;Cimera, 1998;Conley, Rusch, McCaughrin, & Tines, 1989;Hill, Banks, Handrich, Wehman, Hill, & Shafer, 1987;Larson et al, 2007;Rusch, Conley, & McCaughrin, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These variables were selected because of results from previous research that found cost of services, total hours worked, and gross earnings were significantly influenced by the supported employee's gender, disability, presence of a secondary disability, and where they received their services (cf. Cimera, 1998;Cimera, Shumar, Robbins, Dransfield, & Cowan, 2008;Lewis et al, 1992;Thompson, Powers, & Houchard, 1992). Age was also included as a matching variable in an effort to pair individuals with comparable experiences.…”
Section: Analysesmentioning
confidence: 99%
“…Numerous studies have investigated the monetary costs and benefits of supported employment from the perspective of the taxpayers, workers, and society in general (cf. Baer, Simmons, Flexer, & Smith, 1995;Cimera, 1998;Conley, Rusch, McCaughrin, & Tines, 1989;Hill & Wehman, 1983;Kregel, Wehman, & Banks, 1989;McCaughrin, Rusch, Conley, & Tines, 1991;Noble, Conley, Banjerjee, & Goodman, 1991;Rogers, Sciarappa, MacDonald-Wilson, & Danley, 1995;Wehman et al, 2003). Others have compared the programmatic costs of supported employment to those generated by sheltered workshops (cf.…”
mentioning
confidence: 99%
“…A multitude of economic evaluations of SE programs, comparing these to regular vocational training programs etc., has been conducted in the U.S. (Cimera, 1998(Cimera, , 2010a(Cimera, , 2012Conley et al, 1989;Hill & Wehman, 1983;Hill et al, 1987;Latimer, 2001;Rogers et al, 1995). An early European such study, for Wales, is the one by Beyer and Kilsby (1998).…”
Section: Introductionmentioning
confidence: 99%